2010
DOI: 10.1590/2175-7860201061202
|View full text |Cite
|
Sign up to set email alerts
|

Sistema reprodutivo e polinização de Senna multijuga (Fabaceae) em Mata Atlântica Montana

Abstract: ResumoO conhecimento da biologia reprodutiva e polinização de árvores neotropicais vêm aumentando nas últimas décadas. No entanto, ainda é incipiente para a Mata Atlântica e muitas questões persistem, por exemplo, sobre a prevalência de autoincompatibilidade. A biologia floral, o sistema reprodutivo e os visitantes florais de Senna multijuga foram estudados, com o objetivo de verificar a ocorrência de autoincompatibilidade e determinar seus polinizadores. A espécie apresenta características florais típicas do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
0
13
0
3
Order By: Relevance
“…We also detected a significantly higher concentration of sugar in the nectar of less asymmetric plants in burned area. Several studies have shown that FA may be featured as a quantitative and quality indicator of available resources of flowers pollinators (Wignall et al, 2006;Marazzi & Endress, 2008;Wolowski & Freitas, 2010;Potts, 2015). With more symmetrical flowers in the same species as a reliable sign of good quality resources to its visitors (Wignall et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We also detected a significantly higher concentration of sugar in the nectar of less asymmetric plants in burned area. Several studies have shown that FA may be featured as a quantitative and quality indicator of available resources of flowers pollinators (Wignall et al, 2006;Marazzi & Endress, 2008;Wolowski & Freitas, 2010;Potts, 2015). With more symmetrical flowers in the same species as a reliable sign of good quality resources to its visitors (Wignall et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is reinforced by the large number of fruits aborted early during fruit development observed for all of the treatments evaluated in this study. Cases of late self-incompatibility were recorded in Fabaceae species and interpreted as the main cause of fruit abortion (Gibbs and Sassaki, 1998;Rodriguez-Riaño et al, 1999;Freitas and Oliveira, 2002;Leite and Machado, 2010;Wolowski and Freitas, 2010). The effects of this type of incompatibility may be confounded with those of inbreeding depression; the main difference between these two mechanisms is that fruit abscission occurs synchronically in the first, and gradually in the latter (Seavey and Bawa, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…(Carvalho and Oliveira, 2003;Leite and Machado, 2010;Wolowski and Freitas, 2010) and Cassia L. (Bahadur et al, 1979). In the Caesalpinioideae, self-incompatibility is more commonly recorded in tree species with flowers that are characterized by a humid stigma (Arroyo, 1981;Owens and Lewis, 1989), and it is not known if this incompatibility is related to the occurrence of enantiostyly (Bahadur et al, 1979;Carvalho and Oliveira, 2003;Leite and Machado, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Self-incompatibility has been suggested as prevalent in tropical trees (Bawa 1974;Bawa et al 1985b). In fact, several tropical Leguminosae tree species, such as Swartzia pickelli (Lopes & Machado 1996) and Swartzia apetala (Moço & Pinheiro 1999) in the north-eastern Atlantic rainforest, Pseudopiptadenia contorta (Prata-deAssis-Pires & Freitas 2008) and S. multijuga (Wolowski & Freitas 2010) in a montane Atlantic rainforest, Senna silvestris (Carvalho & Oliveira 2003) and Copaifera langsdorffi (Freitas & Oliveira 2002), both in the Brazilian savanna, and Caesalpinia calycina (Lewis & Gibbs 1999) in the caatinga, have been demonstrated as self-incompatible. However, since the number of treated flowers and individuals in this study was low, more experiments are necessary to detect the mating-system of these species.…”
Section: Reproductive Systemmentioning
confidence: 99%
“…The absence of this kind of study is mainly due to difficulties in reaching the flowers in the canopy (Prata-de-Assis-Pires & Freitas 2008;Rocca & Sazima 2008). To our knowledge, only a few studies to date have described the pollinators of some ornithophilous species in the canopy (Rocca et al 2006;Rocca & Sazima 2008), as well as the pollinators and reproductive biology of some melittophilous legume tree species (Borges et al 2008;Prata-de-Assis-Pires & Freitas 2008;Wolowski & Freitas 2010;Amorim et al 2013Amorim et al , Ávila et al 2015, and the bee visitors of some mass flowering tree species (Ramalho 2004;Brito & Sazima 2012).…”
Section: Introductionmentioning
confidence: 99%